1996
DOI: 10.1017/s0021932000022070
|View full text |Cite
|
Sign up to set email alerts
|

The male versus female perspective on family planning: Kinshasa, Zaire

Abstract: Males have often been neglected in both family planning programmes and in surveys used to design and evaluate such programmes. A 1988 study on fertility, family planning and AIDS in Kinshasa, Zaire, provides comparable data on 3140 men and 3485 women of reproductive age which served as the basis for analysing male/female differences. The study indicated a fair degree of similarity in the attitudes, beliefs, knowledge levels and practices of men and women regarding fertility and family planning. Where they diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Comparatively, 49.7% of the males expressed the desire for children than 36.3% female clients. A comparative study in Tigray, Ethiopia (Mesfin, 2002), in South Africa (Cooper et al, 2009) and in Zaire (Bertrand et al, 1996) had showed similar findings that men were found to have greater desire for more children than women. Other finding from SubSaharan Africa also found that African men want to have more children for social and economic gains (Caldwell & Caldwell, 1990).…”
Section: Discussionmentioning
confidence: 82%
“…Comparatively, 49.7% of the males expressed the desire for children than 36.3% female clients. A comparative study in Tigray, Ethiopia (Mesfin, 2002), in South Africa (Cooper et al, 2009) and in Zaire (Bertrand et al, 1996) had showed similar findings that men were found to have greater desire for more children than women. Other finding from SubSaharan Africa also found that African men want to have more children for social and economic gains (Caldwell & Caldwell, 1990).…”
Section: Discussionmentioning
confidence: 82%
“…Men and women have similar attitudes and knowledge levels of contraception (182,183). Currently, however, primary prevention of pregnancy is largely borne by the female partner.…”
Section: Contraceptionmentioning
confidence: 99%
“…28 In sub-Saharan Africa, research into sex preference has largely focused on women's views, to the neglect of men's opinions. [29][30][31][32] In a continent where men are the primary decision-makers (both in public and domestic life) and income earners, reproductive intentions are substantially influenced by their preferences. [33][34][35] This appears especially relevant in the initial stages of a couple's reproductive lives (i.e.…”
Section: Introductionmentioning
confidence: 99%